Isorhynchophylline ameliorates stress-induced emotional disorder and cognitive impairment with modulation of NMDA receptors - Wang, Chen; Zhu, Ming-Hao; Sun, Na; Shen, Wei; Jiang, Ning; Zhao, Qin-Shi; Zhang, Yong-Xiang; Huang, Yan; Zhou, Wen-Xia (Frontiers in Neuroscience, 2022)
Introduction Isorhynchophylline is one of the main active ingredients from Uncaria rhynchophylla, the effects and mechanisms of isorhynchophylline on stress-induced emotional disorders and cognitive impairment remain unclear. Methods Long-term potentiation (LTP) in vivo was used for synaptic plasticity evaluation; chronic unpredictable mild stress (CUMS) model was used to evaluate the effect of isorhynchophylline on stress induced emotional disorders and cognitive impairment; sucrose preference test (SPT), open field test (OFT), and elevated plus maze (EPM) were used to evaluate emotional disorders; morris water maze (MWM) test was used to evaluate cognitive impairment; Western blotting (WB) was used to the expression of proteins; high performance liquid chromatography (HPLC) was used to quantify neurotransmitters; Nissl staining was used to identify pathological changes induced by stress. Results In this study, we found that isorhynchophylline improved corticosterone-induced in vivo LTP impairment significantly, indicating positive effects on stress. Therefore, 28-day CUMS model was adopted to evaluate the anti-stress effects of isorhynchophylline. The results showed that isorhynchophylline improved CUMS-induced weight loss, anxiety- and depression-like behaviors, and spatial memory impairment. Isorhynchophylline reduced CUMS-induced corticosterone elevation. N-methyl-D-aspartic acid (NMDA) receptors play an important role in the process of emotion and memory. Glutamate and the expression of GluN2B increased in the CUMS mice, while D-serine and the expression of serine racemase (SR) decreased significantly, and isorhynchophylline restored these changes to normal level. Conclusion These results indicated that isorhynchophylline ameliorated stress-induced emotional disorders and cognitive impairment, modulating NMDA receptors might be one of the underlying mechanisms.